Chinese symbolism & art motifs a comprehensive handbook on symbolism in Chinese art through the ages - C.A.S. Williams (Charles Alfred Speed) (Tuttle Publishing, 2006)
The Eight Immortals, the five elements, the dragon and the phoenix, yin and yang - presentations of these important cultural symbols are pervasive in Chinese literature, art, and architecture and without an understanding of their significance, much Chinese history, folklore, and culture cannot be fully appreciated. C.A.S. Williams offers concise explanations of these essential symbols and motifs. Arranged alphabetically for easy access, the book not only explains essential cultural symbols, accompanied by their Chinese characters, but also contains many articles on Chinese beliefs, customs, arts and crafts, food, agriculture, and medicine.